Analisis Kualitas Layanan Sistem Informasi Dan Teknologi Informasi Pada Sekolah Tinggi XYZ Dengan Metode IPA - Lisa Amelia; Dorie Pandora Kesuma (Universitas Katolik Musi Charitas, 2020)
This study aimed to analyse the service quality of information system and information technology of XYZ College with Importance Performance Analysis (IPA) method which is used to measure the level of user satisfaction with the services provided. The survey method that is used is questionnaires that were distributed to 200 students at XYZ College and was analyzed by IPA (Importance Performance Analysis) method to determine the level of customer satisfaction that is the gap between importance and performance. The results showed that of the 28 attributes were analyzed by IPA grouped into quadrant I (5 attributes), quadrant II (12 attributes), quadrant III (6 attributes) and quadrant IV (5 attributes).